Reflections of an American composer - Berger, Arthur, 1912-2003 (University of California Press, 2002)
In this collection of essays, distinguished composer, theorist, journalist, and educator Arthur Berger invites us into the vibrant and ever-changing American music scene that has been his home for most of the 20th century.